2008
DOI: 10.1016/j.cub.2008.07.075
|View full text |Cite
|
Sign up to set email alerts
|

The Balance between CONSTANS and TEMPRANILLO Activities Determines FT Expression to Trigger Flowering

Abstract: Seasonal changes in day length influence flowering time in many plant species. In Arabidopsis, flowering is accelerated by exposure to long day (LD). Those inductive photoperiods are perceived in leaves [1] and initiate a long-distance signaling mediated by CO and FT. CO is expressed in the phloem according to a circadian rhythm [2-4]. Only under LD does CO induce FT expression as high levels of CO in the evening coincide with the external light that stabilizes CO protein [4, 5]. Subsequently, FT protein trave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
333
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(363 citation statements)
references
References 21 publications
20
333
1
4
Order By: Relevance
“…AGL24, FPF1, and SPL9 promote flowering (Kania et al, 1997;Melzer et al, 1999;Michaels et al, 2003;Schwarz et al, 2008;Wang et al, 2009), whereas FLC, TEM1, TFL1, MAF2, and MAF3 repress flowering (Michaels and Amasino, 1999;Ratcliffe et al, 2003;Castillejo and Pelaz, 2008).…”
Section: Flowering-time Genesmentioning
confidence: 99%
“…AGL24, FPF1, and SPL9 promote flowering (Kania et al, 1997;Melzer et al, 1999;Michaels et al, 2003;Schwarz et al, 2008;Wang et al, 2009), whereas FLC, TEM1, TFL1, MAF2, and MAF3 repress flowering (Michaels and Amasino, 1999;Ratcliffe et al, 2003;Castillejo and Pelaz, 2008).…”
Section: Flowering-time Genesmentioning
confidence: 99%
“…Under favorable conditions, light signaling and the circadian clock coordinately control the activity of CO, which directly regulates the transcription of FT to promote flowering (Suárez-López et al, 2001;An et al, 2004;Imaizumi et al, 2005;Sawa et al, 2007;Fornara et al, 2009). On the other hand, the expression of FT is also negatively regulated by several transcriptional repressors, such as FLOWERING LOCUS C (Helliwell et al, 2006;Searle et al, 2006), SHORT VEGETATIVE PHASE (Lee et al, 2007), TEMPRANILLO1 (Castillejo and Pelaz, 2008), and SCHLAFMŰTZE (SMZ) (Mathieu et al, 2009). Under unfavorable conditions for flowering or during the juvenile developmental phases, these repressors, as well as their related transcriptional regulators, bind to specific cis-elements in the FT locus and repress its expression to prevent precocious flowering (Song et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that the TEMPRANILLO (TEM) genes have a pivotal role in the direct repression of FT and counteract the activator CONSTANS (CO) 3 . A quantitative balance between TEM and CO, both regulated by light and the circadian clock, controls FT accumulation in LD 3 .…”
mentioning
confidence: 99%
“…A quantitative balance between TEM and CO, both regulated by light and the circadian clock, controls FT accumulation in LD 3 . In addition, it has recently been suggested that GIGANTEA, an output from the circadian clock, directly regulates FT expression through neutralization of TEM (1 and 2) and SHORT VEGETATIVE PHASE 4 , two FT repressors 3,5,6 .…”
mentioning
confidence: 99%